effective application of the principle of brainstorming to the students of the College of Physical Education University of Qadisiyah) - Jabar, Laith (Journal of Physical Education, 2009)
The research contained five sections Covering the first door on the front of research and dealt with by the researcher to the progress of the educational aspects and its impact on improving the educational level and to link the subject of development and brainstorming, which is a form of innovative thinking then was, said the importance of this research and then identify the fundamental problem of identifying the most important research and the main objectives of the Research and Special Assignments with the said areas, which included a search (the human - the spatial - temporal area). The second section in which it was stated by the most important topics that are directly related to the subject of research and brainstorm other. Then comes the third section, which was addressed to the nature of the curriculum when I use the researcher and the nature of the sample, means and devices Almskhaddmp and push the search form with an indication of the exploratory experiments and then he mentioned the main statistical tools used by the researcher. Followed by Part IV, which includes the presentation of the results reached by the researcher using the questionnaire form and the extraction of data for each of the values and compare their own spreadsheet and then came the process of discussing the results through the identification of Manoitha not discuss the results were Manoitha moral only. Then comes the fifth and final section included Conclusions, namely: 1. The presence of a very strong relationship between the psychological barriers and the student himself and this impacts negatively on the march of science. 2. There is a moral sense of rights also relate to the need to compromise with others and must be studied and developed in all respects. 3. The existence of a moral relationship between the student and the fear of accusations of other ridiculous ideas. The recommendations included: 1. The need to raise the fear factor in the final of the student and this will not come easily, but the development of new programs the development of thinking and lack of fear. 2. The need to get the students to adhere to their views were correct and that their views and suggestions. 3. The need for further studies, such as how the methods of learning. 4. The need to establish a program for Brainstorming starts the beginning of direct student attendance for the development of formal plans for the future and to do so.